Analysis of Volatile Constituents of Perovskia abrotanoides with Different Extraction Methods - Abroomand Azar, Parviz; Torabbeigi, Marzieh; Sabertehrani, Mohammad; Waqif Husain, Seyed (Asian Journal of Chemistry, 2010)
In this study, three new methods, solvent free microwave extraction (SFME), head-space solidphase microextraction (HS-SPME) and microwave assisted head-space solid-phase microextraction (MW-HS-SPME), were developed for the analysis of essential oil compounds in aerial part and flower of Perovskia abrotanoides. Then these methods were compared with traditional extraction method of essential oil, hydrodistillation (HD). The extraction conditions of these methods were optimized. The optimum conditions for these methods were: 500 W power of microwave and 0.5 h the extraction time for SFME method, 70 ºC and 5 min exposure time for HS-SPME method (with PDMS fiber) and 400 W power and 5 min exposure time for MW-HS-SPME method.